2021
DOI: 10.21203/rs.3.rs-806303/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Returning to Work After a Sickness Absence Due to Cancer: A Cohort Study of Salaried Workers in Catalonia (Spain)

Abstract: Background: Cancer incidence and survival rates have increased in the last decades and as a result, the number of working age people diagnosed with cancer who return to work. In this study the probability of accumulating days of employment and employment participation trajectories (EPTs) in a sample of salaried workers in Catalonia (Spain) who had a sickness absence (SA) due to cancer were compared to salaried workers with SA due to other diagnoses or without SA.Methods: Each individual with SA due to cancer b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Literature shows cancer survivors have more frequent sick leaves and worse job retention than the general population. 5,10 The proportion of cancer survivors working peaks at 3-4 years after diagnosis and then decreases again. 5,33 While most studies have studied RTW, [5][6][7]9,16 our study investigates job trajectories after BC in more detail and adds to the literature by documenting SRTW among BCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature shows cancer survivors have more frequent sick leaves and worse job retention than the general population. 5,10 The proportion of cancer survivors working peaks at 3-4 years after diagnosis and then decreases again. 5,33 While most studies have studied RTW, [5][6][7]9,16 our study investigates job trajectories after BC in more detail and adds to the literature by documenting SRTW among BCS.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the challenge goes beyond return to work (RTW) and sustainable RTW (SRTW) is an issue for many BCS who often have several sick leaves or struggle to retain their jobs after RTW. [6][7][8][9][10] Employment after cancer can be affected by different factors. Evidence from studies including survivors from all cancer sites found that clinical factors, sociodemographic factors, including older age, low socio-economic status, workplace environment (e.g.…”
Section: Introductionmentioning
confidence: 99%